A long wait: barriers to discharge for long length of stay patients. Issue 1116 (9th October 2018) - Zhao, Emma Jane; Yeluru, Apurva; Manjunath, Lakshman; Zhong, Lei Ray; Hsu, Hsiao-Tieh; Lee, Charles K; Wong, Anny C; Abramian, Matthew; Manella, Haley; Svec, David; Shieh, Lisa
Abstract: Introduction: Reducing long length of stay (LLOS, or inpatient stays lasting over 30 days) is an important way for hospitals to improve cost efficiency, bed availability and health outcomes. Discharge delays can cost hundreds to thousands of dollars per patient, and LLOS represents a burden on bed availability for other potential patients. However, most research studies investigating discharge barriers are not LLOS-specific. Of those that do, nearly all are limited by further patient subpopulation focus or small sample size. To our knowledge, our study is the first to describe LLOS discharge barriers in an entire Department of Medicine. Methods: We conducted a chart review of 172 LLOS patients in the Department of Medicine at an academic tertiary care hospital and quantified the most frequent causes of delay as well as factors causing the greatest amount of delay time. We also interviewed healthcare staff for their perceptions on barriers to discharge. Results: Discharge site coordination was the most frequent cause of delay, affecting 56% of patients and accounting for 80% of total non-medical postponement days. Goals of care issues and establishment of follow-up care were the next most frequent contributors to delay. Conclusion: Together with perspectives from interviewed staff, these results highlight multiple different areas of opportunity for reducing LLOS and maximising the care capacity of inpatient hospitals.